2007
DOI: 10.1111/j.1601-5037.2007.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonic and ultrasonic scalers in periodontal treatment: a review

Abstract: Periodontal therapy aims at arresting periodontal infection and maintaining a healthy periodontium. The periodic mechanical removal of subgingival microbial biofilms is essential for controlling inflammatory periodontal disease. Mechanical periodontal therapy consists of scaling, root planing and gingival curettage. The sonic and ultrasonic scalers are valuable tools in the prevention of periodontal disease. The vibration of scaler tips is the main effect to remove the deposits from the dental surface, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 89 publications
0
93
2
3
Order By: Relevance
“…6-8). Arabaci et al (2007) found that the piezoelectric system was more efficient in calculus removal compared to magnetostrictive and hand instrumentation, but they left tooth surface rougher. Other studies have shown contradictory results with each other.…”
Section: Ultrasonic Instrumentsmentioning
confidence: 97%
“…6-8). Arabaci et al (2007) found that the piezoelectric system was more efficient in calculus removal compared to magnetostrictive and hand instrumentation, but they left tooth surface rougher. Other studies have shown contradictory results with each other.…”
Section: Ultrasonic Instrumentsmentioning
confidence: 97%
“…This is consistent with the explanation that the increase in temperature of ultrasonic scaling can damage the pulp and disrupt circulatory system resulting in dental pulpitis or necrosis. 11 The effects caused by ultrasonic wave exposure to tissue is thermal, mechanical (cavitation and microstreaming), and chemical (sonochemistry). Clinical effect is depending on the application technique used.…”
Section: Resultsmentioning
confidence: 99%
“…Alet ucu 25000-45000 saykıllık (cycles) frekanslarda titreşerek sert eklentilerin kırılıp parçalan-masına yol açar. Bu arada oluşan ısıyı önlemek üzere çalışmayla eşzamanlı su fışkırtılır 12 .…”
Section: Ultrasonik Ve Sonik Aletlerle Yapılan Diş Taşı Temizliği Ve unclassified